Art pedigree of different periods (Eurasian Journal of Philology Science and Education, 2016)
The article says Кodeк Maralbayuly poems, in which he wrote about the national liberation uprising in 1916. One of them is a poem «1916», and the second is «Sagynysh tolgauy». The author highlights the Kodek from all other poets who have written about the hard life in his time. In an article he wrote about the poem that spoke of the unfair from the government, and the times of the civil war, warriors, living away from their homeland, about the suffering of the people. The Kodek clearly expressed the truth about people’s liberation (STL-Azattyk) revolts gave rise to colonization. The works of the poet about the life of the people of those times was considered and studied, along with the works of other poets
Keywords: Kazakhrhyme; poem; poet; of national liberation uprising; verse(poem); the truth of life; creation.